Interfacial reactivity of ``on water'' reactions in the presence of alcoholic cosolvents - Tiwari, Shraeddha; Kumar, Anil (Journal of Physical Chemistry A, 2009)
A detailed study of the variation in the interfacial reactivity and selectivity of ``on water'' reactions in the presence of increasing amounts of alcoholic cosolvents is discussed in the present work. The initial increase in the rates of ``on water'' reactions on the addition of alcoholic cosolvents is contrary to the sharp decrease in rates observed for homogeneous aqueous reactions. The existing theoretical framework is presented in terms of a typical ``on water'' process to enable a discussion of the experimental observations with reference to changing composition of the reaction medium. On the basis of the interesting observations of reactivity and selectivity variations with composition of the reaction medium, a simple ``signature'' characteristic for ``on water'' reactions is proposed.